2007
DOI: 10.1002/jat.1210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined exposure to pyridostigmine bromide and shaker stress on acoustic startle response, pre‐pulse inhibition and open field behavior in mice

Abstract: The present study investigated the effect of combined exposure of pyridostigmine bromide (PB) and chronic shaker stress on acoustic startle responses (ASR), pre-pulse inhibition (PPI) and open field behavior of adult C57BL/6J mice. PB (10 mg kg(-1) day(-1) for 7 days) or saline was administered subcutaneously using osmotic Alzet minipumps implanted under the skin on the back of the mice. At the same time, the mice were exposed to 7 days of intermittent shaker stress. They were tested for ASR (100 dB and 120 dB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Although the advantages of pyridostigmine has been shown both in health (Nóbrega et al 1996Castro et al 2000;Sant'anna et al 2003) and in patients with heart failure (Castro et al 2002(Castro et al , 2004(Castro et al , 2006Nóbrega et al 2008;Serra et al 2009), side effects characterized mainly by intestinal distress were observed with a daily oral dose of 5 mg/kg for 3 months, and the dose of 20 mg/kg was lethal to dogs when given for up to 14 days (Kluwe et al 1989). Furthemore, combined exposure of mice to 10 mg/kg/day of pyridostigmine bromide and shaker stress for 7 days resulted in neurobehavioral changes such as sensorimotor alterations and decreased locomotor activity (Dubovicky et al 2007). That same dose of pyridostigmine caused to male mice adverse influence on cardiac growth and vascular structure, specifically reduction of the aortic wall thickness/diameter ratio and reduced relative heart weight (Bernátová et al 2006).…”
Section: Discussionmentioning
confidence: 92%
“…Although the advantages of pyridostigmine has been shown both in health (Nóbrega et al 1996Castro et al 2000;Sant'anna et al 2003) and in patients with heart failure (Castro et al 2002(Castro et al , 2004(Castro et al , 2006Nóbrega et al 2008;Serra et al 2009), side effects characterized mainly by intestinal distress were observed with a daily oral dose of 5 mg/kg for 3 months, and the dose of 20 mg/kg was lethal to dogs when given for up to 14 days (Kluwe et al 1989). Furthemore, combined exposure of mice to 10 mg/kg/day of pyridostigmine bromide and shaker stress for 7 days resulted in neurobehavioral changes such as sensorimotor alterations and decreased locomotor activity (Dubovicky et al 2007). That same dose of pyridostigmine caused to male mice adverse influence on cardiac growth and vascular structure, specifically reduction of the aortic wall thickness/diameter ratio and reduced relative heart weight (Bernátová et al 2006).…”
Section: Discussionmentioning
confidence: 92%
“…) produced an exaggerated ASR and reduced PPI (Dubovicky et al, 2007). The changes were apparent only during exposure to PB and returned to control values after discontinuation of the treatment.…”
Section: Discussionmentioning
confidence: 60%
“…In contrast to ASR, where differences between cholinesterase inhibitors and species differences were found, locomotor activity was depressed in a similar fashion across different classes of cholinesterase inhibitors and different species (Philippens et al, 1996(Philippens et al, , 1997Jones and Shannon, 2000;Nieminen et al, 1990;Mach et al, 2004;Scremin et al, 2005, Dubovicky et al, 2007. This indicates a central role of the cholinergic system in the regulation of locomotor activity.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…For example, exposure to stress or stress hormones decreases PPI in rodents (Conti, Murry, Ruiz, & Printz, 2002; Risbrough, Hauger, Roberts, Vale, & Geyer, 2004; Sutherland, Burian, Covault, & Conti, 2010; Sutherland & Conti, 2011), although not all studies find disruptive effects of stress on PPI (Dubovicky, Paton, Morris, Mach, & Lucot, 2007; Faraday, O'Donoghue, & Grunberg, 1999; Pijlman, Herremans, van de Kieft, Kruse, & van Ree, 2003). Evidence of acute alcohol effects on PPI in rodents is sparse, but Jones and colleagues (2000) showed that alcohol disrupts PPI for female P rats but not NP rats, suggesting differential sensitivity to the effects of acute alcohol on PPI that is influenced by genetic susceptibility for high- or low-alcohol preference.…”
Section: Introductionmentioning
confidence: 99%